Fracture patterns of the drainage basin of Wadi Dahab in relation to tectonic-landscape evolution of the Gulf of Aqaba - Dead Sea transform fault. (15th October 2017) - Shalaby, Ahmed
Graphical abstract: Highlights: Morphotectonics of the Gulf of Aqaba region are delineated and analyzed. The fracture pattern and the drainage system of Wadi Dahab are evolved since Oligo-Miocene to Pleistocene. Formation of the Afro-Arabian rifts is controlled by trends of the Precambrian fabrics. Abstract: Crustal rifting of the Arabian-Nubian Shield and formation of the Afro-Arabian rifts since the Miocene resulted in uplifting and subsequent terrain evolution of Sinai landscapes; including drainage systems and fault scarps. Geomorphic evolution of these landscapes in relation to tectonic evolution of the Afro-Arabian rifts is the prime target of this study. The fracture patterns and landscape evolution of the Wadi Dahab drainage basin (WDDB), in which its landscape is modeled by the tectonic evolution of the Gulf of Aqaba-Dead Sea transform fault, are investigated as a case study of landscape modifications of tectonically-controlled drainage systems. The early developed drainage system of the WDDB was achieved when the Sinai terrain subaerially emerged in post Eocene and initiation of the Afro-Arabian rifts in the Oligo-Miocene. Conjugate shear fractures, parallel to trends of the Afro-Arabian rifts, are synthesized with tensional fracture arrays to adapt some of inland basins, which represent the early destination of the Sinai drainage systems as paleolakes trapping alluvial sediments. Once the Gulf of Aqaba rift basin attains its deeps through sinistral movements on the Gulf of Aqaba-Dead Sea transform fault in the Pleistocene and the consequent rise of the Southern Sinai mountainous peaks, relief potential energy is significantly maintained through time so that it forced the Pleistocene runoffs to flow via drainage systems externally into the Gulf of Aqaba. Hence the older alluvial sediments are (1) carved within the paleolakes by a new generation of drainage systems; followed up through an erosional surface by sandy- to silty-based younger alluvium; and (2) brought on footslopes of fault scarps reviving the early developed scarps and inselbergs. These features argue for crustal uplifting of Sinai landscapes syn-rifting of the Gulf of Aqaba rift basin. Oblique orientation of the Red Sea-Gulf of Suez rift relative to the WNW-trending Precambrian Najd faults; and extrusion of volcanic rocks in directions parallel to the rift boundaries geometrically suggest rifting on tensional fractures that mutually bridge the Najd fault-related shear fractures. These aspects might envisage reactivation of the preexisting Precambrian fracture patterns in the Arabian-Nubian shield by the Oligo-Miocene to Pleistocene rift-controlled stress field.